'Speaking English naturally': the language ideologies of English as an official language at a Korean university. Issue 8 (16th November 2016) - Choi, Jinsook
ABSTRACT: This study explores language ideologies of English at a Korean university where English has been adopted as an official language. This study draws on ethnographic data in order to understand how speakers respond to and experience the institutional language policy. The findings show that language ideologies in this university represent the institutional norms and expectations of English. The interpretive frame used to respond to the policy is best represented by the discourse of 'speaking English naturally'. While some informants are positive that the language policy will enable them to transform themselves into competent speakers of English, others are sceptical about the effect of the policy in everyday communication, including classroom activities and interaction with international members of the university. Hence, within the space of interactions demarcated by the university, the ideology of English hegemony has contradictory effects upon the patterns and the rationales of language choice in routine situations. This case study illustrates important dilemmas and confusion in social interactions that typically occur in Korea when spaces are designated for English use, because the space of English as an official language is primarily linked with the language ideology of monolingualism.